A wiser century? : judicial dispute settlement, disarmament and the laws of war 100 years after the Second Hague Peace Conference - Giegerich, Thomas; Heinz, Ursula E., 1947- (Veröffentlichungen des Walther-Schücking-Instituts für Internationales Recht an der Universität Kiel, 2009)
Hauptbeschreibung The Hague Peace Conferences of 1899 and 1907 dealt with three interlinked topics: the peaceful settlement of disputes, including by arbitration; the restriction of armaments and military budgets; the laws of war. The first two were aimed at preventing the outbreak of war, not by restricting the jus ad bellum in its substance, but by inducing states not to use their continuing war power and to limit the growth of their war machinery. The third topic was concerned with containing the brutality of war where its prevention had failed. Whereas the Conferences succeeded.